2009
DOI: 10.2320/matertrans.m2009225
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sintering Temperature on Thermoelectric Device of La-Doped Strontium Titanate in the Combination of Combustion Synthesis and Spark Plasma Sintering

Abstract: Thermoelectric properties of La-doped SrTiO 3 were investigated in order to determine the optimum sintering temperature for its fabrication by using a combination of combustion synthesis and spark plasma sintering. Combustion-synthesized samples (Sr 1Àx La x TiO 3 , x ¼ 0:08) were subjected to spark plasma sintering at temperatures from 1513 to 1663 K. The average grain size of sintered Sr 0:92 La 0:08 TiO 3 enlarged as sintering temperature rose up. The maximum average grain size was 23.5 mm for a sintering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…There is no difference between the XRD patterns obtained before and after SPS, indicating that secondary-phase has not appeared during sintering. Also, we confirmed that the SEM image 22) didn't show secondary-phase in SPSed products. Figures 2(a), (b) and (c) show the temperature dependence of , and of CSed and SPSed SLTO for various sintering temperatures, respectively.…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…There is no difference between the XRD patterns obtained before and after SPS, indicating that secondary-phase has not appeared during sintering. Also, we confirmed that the SEM image 22) didn't show secondary-phase in SPSed products. Figures 2(a), (b) and (c) show the temperature dependence of , and of CSed and SPSed SLTO for various sintering temperatures, respectively.…”
Section: Resultssupporting
confidence: 73%
“…22) The average grain size of SLTO sintered at 1513, 1543, 1573, 1603, 1633, and 1663 K was approximately 1.32, 4.31, 3.61, 2.32, 6.63, and 23.5 mm, respectively. 22) The average grain size of sintered SLTO decreased above 1573 K, but it increased again above 1603 K. In experimental sintering temperature range, sintering temperature didn't heavily affect the average grain size of sintered SLTO in the case of sintering temperature ranges from 1543 to 1603 K. However, when sintering temperature rose over 1603 K, the average grain size of sintered SLTO was dramatically affected and it increased with sintering temperature. Table 1 lists the lattice parameters of synthesized powders before SPS calculated from XRD data and comparison of sintering temperatures and bulk density after SPS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For x 0.10, the power factor exhibits similar behaviour with that observed for Sr 1 x La x TiO 3 and La 0.1 Sr 0.9 x Dy x TiO 3 ceramics. 17,22,40 The maximum power factor of $1400 lW m 1 K 1 at 670 K was observed for Sr 0.90 Pr 0.10 TiO 3 , in accordance with the trends …”
Section: -3supporting
confidence: 71%